2021
DOI: 10.25259/sni_415_2021
|View full text |Cite
|
Sign up to set email alerts
|

Effect of comorbidities on ischemic stroke mortality: An analysis of the National Inpatient Sample (NIS) Database

Abstract: Background: Stroke risk has been attributed to many pathological and behavioral conditions. Various modifiable and non-modifiable risk factors have been recognized and found consistent throughout epidemiological studies. Herein, we investigate the effect of comorbidities seen with patient’s suffering from ischemic stroke and its effect on in-hospital mortality. Methods: We identified patients >18 year old in the National Inpatient Sample database with diseases of interest utilizing the tenth Internation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 9 publications
(23 reference statements)
0
3
0
Order By: Relevance
“…The hospitalization-related mortality rate of patients with AIS complicated by ischemic heart disease is approaching 30% [11]. Complex cardiovascular disease accounts for approximately 20% of post-stroke deaths, making it the second most frequent cause of post-stroke death after neurological death [7,12].…”
Section: Epidemiology Of Stroke-heart Syndromementioning
confidence: 99%
“…The hospitalization-related mortality rate of patients with AIS complicated by ischemic heart disease is approaching 30% [11]. Complex cardiovascular disease accounts for approximately 20% of post-stroke deaths, making it the second most frequent cause of post-stroke death after neurological death [7,12].…”
Section: Epidemiology Of Stroke-heart Syndromementioning
confidence: 99%
“…Other researchers have focused on predicting the severity and risk of mortality during admission for ischaemic stroke, in line with our own study goals. In one notable case [30], the US National Inpatient Sample (NIS) database was analysed using the main clinicaladministrative variables recorded in ICD-10 and for the same time period (2016)(2017)(2018). This paper concluded that in-hospital mortality due to ischaemic stroke was significantly associated with atrial fibrillation, carotid stenosis, diabetes, heart failure, and ischaemic heart disease.…”
Section: Comparison With Previous Studiesmentioning
confidence: 99%
“…Hospital-acquired infections, such as urinary tract infections and pneumonia, have been noted as significant factors in forecasting stroke prognosis, and mortality [ 12 , 27 ]. In addition to clinical findings and stroke severity upon presentation, patients' comorbid conditions, such as diabetes mellitus (DM), hypertension (HTN), dyslipidemia, prior stroke, coronary artery disease (CAD), history of atrial fibrillation (AF), or congestive heart failure (CHF), have demonstrated substantial predictive roles in shaping stroke patients' prognosis, including disabilities and mortality [ 21 , 22 , 25 , 28 ]. Further factors, such as decrease in the duration from stroke onset to hospital arrival, prompt intervention, especially thrombolysis for IS, increases the chances of a favorable prognosis [ [29] , [30] , [31] ].…”
Section: Introductionmentioning
confidence: 99%